Association of Genetic Variants With Rivaroxaban Pharmacokinetics and Pharmacodynamics and Hemorrhage Risk Factors in Patients With Venous Thromboembolism - Hui Li; Xiaoshuang He; Yingyun Guan; Qiuya Lu; Jie Fang; Xiaolan Bian (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Rivaroxaban is a first‐line agent for venous thromboembolism prophylaxis and treatment. However, its pharmacokinetics, pharmacodynamics, and bleeding risk exhibit significant interindividual variability. Known nongenetic factors alone cannot fully explain this variability, and the impact of genetic polymorphisms remains debated. Methods From December 29, 2021, to May 11, 2023, 310 patients with venous thromboembolism treated with rivaroxaban were enrolled in this observational study from a tertiary hospital in Shanghai, China, based on predefined criteria. We assessed relationships between rivaroxaban concentrations, anti‐Factor Xa levels, and coagulation parameters; examined the impact of 12 genes on concentrations and anti‐Factor Xa levels; and followed up for at least 3 months to identify bleeding risk factors. Results Rivaroxaban plasma concentration was significantly related to anti‐Factor Xa levels (R2=0.697), activated partial thromboplastin time (R2=0.134), prothrombin time (R2=0.123), and international normalized ratio (R2=0.116). Peak concentrations were associated with cytochrome p4503A5 (rs776746, P=0.023), sushi domain‐containing protein 3 ( rs76292544, P=0.034), and ATP‐binding cassette subfamily G member 2 ( rs1045642, P=0.012); trough concentrations were linked to cytochrome p4503A5 (rs776746, P=0.045), sushi domain‐containing protein 3 (rs76292544, P=0.014), and ATP‐binding cassette subfamily G member 2 (rs2231142, P=0.029); peak anti‐Factor Xa levels were associated with aldo‐keto reductase family 7 member A3 (rs1738023, P=0.022; rs1738025, P=0.035) and ATP‐binding cassette subfamily A member 6 (rs7212506, P=0.044). However, these genetic associations were not significant after Bonferroni correction. Hemorrhage risk factors were anemia, pulmonary embolism, and the TT genotype of sushi domain‐containing protein 3 (rs76292544). Conclusions Pharmacogenetic monitoring and hemorrhage risk assessment may contribute to optimize its efficacy and safety. Larger‐scale, global multicenter clinical trials are required to validate the potential gene loci for testing, including cytochrome p4503A5 (rs776746), sushi domain‐containing protein 3 (rs76292544), ATP‐binding cassette transporter B1 (rs1045642), and ATP‐binding cassette subfamily G member 2 (rs2231124), with particular focus on sushi domain‐containing protein 3 (rs76292544).